Mandat Ilahi dalam Hukum Kasih Menurut Matius 22:39 - Elkana, Samuel (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
God's command to obtain eternal life is by doing the law of love. The mandate to love God and neighbor was given to mankind. Sometimes humans fail to carry out the divine mandate regarding the law of love because of a lack of understanding of the law of love. This research explains comprehensively and theologically by using qualitative methods, namely literature studies.